PROTOTIPE SMART SEATBELT DAN AUTO SPEED CONTROL PADA HYDRAULIC EXCAVATOR - Edwin Fitrian; Samuel H. Tirtamihardja (Website, 2018)
In this research, two types of mechanical system in hydraulic excavator type PC 3000-6, which are smart seatbelt and automatic (auto) engine speed control, were developed to enforce operator’s safety and maintain engine fuel efficiency. There are conditions where sometimes operators do not use their seatbelt for safety and do not use auto engine speed control appropriately which affect fuel consumption efficiency in the hydraulic excavator. Smart seatbelt prototipe and auto engine speed control were designed using Arduino Uno as the controller. Smart safety belt was designed with proximity sensor as seatbelt condition detector to check its condition whether it is in use or unplugged. When the proximity sensor detects that the seatbelt is not in use, then the microcontroller will give a command not to turn on the starting motor (DC motor) although the starting switch is in start position. The auto engine speed control uses a potentiometer that regulates the engine speed (DC motor) which is based on the joystick movement. When the engine (DC motor) is in a state of maximum rotation but the joystick is not moved, then the auto rotation turns to minimum condition. As the conclusion of this research, the proximity sensor can detect the seatbelt condition according to the design, and the auto speed control works automatically for controlling engine speed in maximum and minimum conditions. By using auto speed control engine, it is concluded that the fuel consumption saving is up to 26.35%. Pada penelitian ini dikembangkan dua sistem mekanik yaitu seatbelt dan automatic (auto) engine speed control pada hydraulic excavator jenis PC 3000-6. Terdapat permasalahan bahwa terkadang operator tidak menggunakan seatbelt untuk keselamatan dan tidak menggunakan auto speed control engine sesuai dengan kebutuhan yang berpengaruh pada efisiensi pemakaian bahan bakar pada hydraulic excavator. Prototipe smart seatbelt dan auto engine speed control dirancang menggunakan Arduino Uno sebagai kontroler. Smart seatbelt dirancang dengan sensor proximity sebagai pendeteksi seatbelt pada keadaan terpasang dan tidak terpasang. Apabila sensor proximity mendeteksi seatbelt pada keadaan tidak terpasang maka mikrokontroler akan memberikan perintah untuk tidak menghidupkan starting motor (motor DC) meskipun starting switch pada posisi start. Perancangan auto engine speed control menggunakan potensiometer yang mengatur kecepatan engine (motor DC) tetapi dipengaruhi oleh pergerakan joystick. Walaupun setting engine (motor DC) dalam keadaan putaran maksimum namun jika joystick tidak digerakkan maka putaran otomatis menjadi minimum. Hasil pengujian sensor proximity dapat mendeteksi keadaan seatbelt sesuai perancangan alat ini. Selain itu, auto speed control dapat bekerja secara otomatis untuk mengendalikan putaran engine pada saat keadaan maksimum dan minimum. Penghematan fuel consumption didapatkan hingga 26,35 % dengan menggunakan auto engine speed control.